Drought and the risk of hospital admissions and mortality in older adults in western USA from 2000 to 2013: a retrospective study. Issue 1 (April 2017) - Berman, Jesse D; Ebisu, Keita; Peng, Roger D; Dominici, Francesca; Bell, Michelle L
Summary: Background: Occurrence, severity, and geographic extent of droughts are anticipated to increase under climate change, but the health consequences of drought conditions are unknown. We estimate risks of cardiovascular-related and respiratory-related hospital admission and mortality associated with drought conditions for the elderly population in western USA. Methods: For this retrospective study, we analysed the 2000 to 2013 data from the US Drought Monitor for 618 counties in the western USA to identify full drought periods, non-drought periods, and worsening drought periods stratified by low severity and high severity. We used Medicare claims made between Jan 1, 2000, and Dec 31, 2013, to calculate daily rates of cardiovascular admissions, respiratory admissions, and deaths among adults aged 65 years or older. Using a two-stage hierarchical model, we estimated the percentage change in health risks when comparing drought with non-drought period days, controlling for daily weather and seasonal trends. Findings: On average, 2·1 million days were classified as non-drought periods and 0·6 million days were classified as drought periods. Compared with non-drought periods, respiratory admissions significantly decreased by −1·99% (95% posterior interval −3·56 to −0·38) during the full drought period, but not during worsening drought conditions. Mortality risk significantly increased by 1·55% (0·17 to 2·95) during the high-severity worsening drought period, but not the full drought or low-severity worsening drought periods. Cardiovascular admissions did not differ significantly during either full drought or worsening drought periods. In counties where drought occurred less frequently, we found risks for cardiovascular disease and mortality to increase during worsening drought conditions. Interpretation: Drought conditions increased risk of mortality during high-severity worsening drought, but decreased the risk of respiratory admissions during full drought periods among adults aged 65 years and older. Counties that previously had fewer drought events show larger risk for mortality and cardiovascular disease. This research describes an understudied environmental association with global health significance. Funding: The Yale Institute of Biospheric Studies, the National Institute of Environmental Health Sciences, the US Environmental Protection Agency.